KESEJAHTERAAN SUBJEKTIF PADA INDIVIDU BERCERAI (STUDI KASUS PADA INDIVIDU DENGAN STATUS CERAI MATI DAN CERAI HIDUP) - Nadhira Miranda; Zaujatul Amna (Psikoislamedia : Jurnal Psikologi, 2017)
Divorce is the termination of a marriage or marital union, the canceling and/or reorganizing of the legal duties and responsibilities of marriage as husband and wife. Moreover, divorce can also be interpreted as the status of an individual who lives separately with his/her spouse is deceased and not remarried. Individuals who get divorced has a high or low levels on subjective well-being. It is influenced by several factors such as employments and income levels, social support also religiosity. The research aimed to seek the dynamics of subjective well-being on individuals’ divorced. 50 individuals were selected using purposive and quota sampling technique as research participants. Data collected using Satisfaction with life scale (SWLS) and Positive and negative experience Scale (SPANE). Data was analyzed by using Independent sample T-test, which value of significance (p) = 0.669 (p> 0.005), which means that there were no differences in subjective well-being in individual’s divorced with Widowed and Divorced status.